Diskursus Sosial Stakeholder dalam Upaya Pelestarian Sumber Daya Alam (UPSA) di Kabupaten Malang: Stakeholder Social Discourse in Natural Resource Conservation (UPSA) Efforts in Malang District - Muttaqin, Tatag; Sukmawati, Musdzalifah; Bala, Imam Ade Putra; Pradipta, Naresvara Nircela (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
UPSA (The Natural Resources Conservation Effort is one of BPDAS Brantas Sampean’s RHL (Forest and Land Rehabilitation) progams which are carried out in 3 places namely Pujon Hill, UB Forest and Wajak, Malang Regency. Collaboration between stakeholder is the main key to the succes of policy produts and their sustainability. Discourse is present as a tool that is able to provide an explanation of sosial conditions. Aim of this research is how the perspectiveof stakeholder influences the follow-up action pf the progam. Data collection uses observation, interviews document analysis related to UPSA. Discourses analysis begins with the result of interviews that have been recorded and then transcribed into writing and data analysis by the Nvivo12 software. The result of the data re then explained descriptively. Our findings show that the perspective of each stakeholder towards the UPSA Progam Influences land management. The Occurrence of domination of power, a sense of ownership and openness among stakeholders has the potential to create new conflicts. Keywords : Social Discourse, Stakeholder, UPSA